The essence of the technical and vocational education in different historical periods (Pedagogy of Higher and Secondary Education, 2012)
Zhavoronkov A. The essence of the technical and vocational education in different historical periods.In the article the essence of vocational education and its role in the development of the state. The critical analysis of the term «vocational education», used in different historical periods. Formulated and justified the author’s vision of the concept. Adapted role of vocational education to the modern economic conditions.
Keywords: vocational education; terminology; historical experience